USING NON-INVASIVE BIOMARKERS AND PLACE OF CYTOKERATIN 18 IN DIAGNOSIS PATIENTS WITH NON-ALCOHOLIC FATTY LIVER DISEASE - N. V. Dynnyk (Bogomolets National Medical University, 2016)
The aim of this study was: 1.Determination of optimum degree of non-invasive diagnostic methods steatosis and liver fibrosis in clinical practice. 2. Determination of the diagnostic value of the CK 18, compared with clinical biomarkers of the degree of steatosis, inflammation and fibrosis of the liver. 3. Implementation of the correlation analysis of the CK 18 with anthropometric data and the relative content of fat in the organism by a bioelectrical impedance. We investigated 50 patients. Inclusion criteria in the study: patients with an established diagnosis of non-alcoholic fatty liver disease according to current national and international protocols, age-range 18-65 years. The study used the following methods: general clinical examination methods - history taking, examination of the patient; Anthropometric, Clinical and laboratory indices, Biochemical, Reagents Human, analyzer Humalyser 2000 M30 fragments of cytokeratin 18 by TPS- Elisa reagents - ELISA (tissue polypeptide specific antigen, cytokeratin 18 IDL), Instrumental metods. We have used content analysis, method of systematic and comparative analysis in studying the current 73 scientific studies published in English or Ukrainian (PubMed-NCBI, Medline, CochraneLibrary, EMBASE, ResearchGate), of which selected 25 works which used non-invasive methods of diagnosis with proven high sensitivity and specificity in diagnosis NAFLD. The results: During the correlation analysis of the level of the CK 18 and clinical indices of the degree of steatosis assessment of a direct strong correlation between clinical indices of the degree of hepatic steatosis Steatotest (r = 0,76, p <0,05), FLI (r = 0,74 p < 0.05) and the level of CK18 that suggests pathogenetic role of apoptosis in NAFLD. In assessing the degree of inflammation in these patients using the NASH- test - a direct strong correlation (r = 0,72, p <0,05) with the CK 18 level, even with normal transaminases, indicating the predictive value of the CK18 in developing NASH. At the same time it found no correlation CK 18 with a degree of liver fibrosis determined by a NAFLD-fibrosis score and shear wave elastography using ultrasound, indicative of independent diagnostic value of the CK 18 level. Several non-invasive methods aim at diagnosing and quantifying hepatic steatosis, while others were designed to predict NASH or significant/advanced fibrosis. Ultrasonography still represents the first-line diagnostic tool for simple liver steatosis; its sensitivity could be enhanced by the complex biochemical scores. Serum cytokeratin-18 is a promising and accurate non-invasive parameter for the diagnosis of non-alcoholic steatohepatitis (NASH). The staging of liver fibrosis still represents the most important prognostic problem: the most accurate estimating methods are FibroMeter, FIB-4, NAFLD fibrosis score and transient elastography. Conclusions: Among non-invasive instrumental methods of diagnosis of hepatic steatosis is optimal ultrasonic diagnostic method. Among the clinical and laboratory indices the highest sensitivity and specificity have Fatty liver index and Steatotest to assess the degree of liver steatosis and for the assessing the degree of liver fibrosis - NAFLD-fibrosis score. To predict the development of nonalcoholic steatohepatitis are the most sensitive NASH-test and determination of non-invasive biomarkers of inflammation and apoptosis cytokeratins 18 M30 fragments.CK 18 can be an independent non-invasive biomarker for predicting the degree of steatosis and NASH in patients with visceral obesity and normal level of transaminases. Determination CK18 may be not only diagnostic marker and also can be used as a marker of evaluating the effectiveness of treatment in dynamics.